News Deserts: A Research Agenda for Addressing Disparities in the United States - Abernathy, Penelope Muse (2023)
News deserts are spread unevenly across the US, with as much as a fifth of the country’s population handicapped by a lack of access to critical news and information. There is a prodigious amount of recent research outlining the consequences for democracy. However, as policymakers, philanthropists, and entrepreneurs devise solutions, they are encountering gaps in information that hinder their ability to address the news disparities among communities. We need a focused research agenda that assists stakeholders in identifying the communities most at risk, understanding the current flow of critical news and information in communities without a local news provider, and establishing sustainable business models for existing and start-up organizations in both current news deserts and at-risk communities.